Risk Factors for Perineal Rupture in Normal Maternity Women at Midwife Independent Practice (BPM) Barirah Madeni, Bebesen District, Central Aceh Regency, Indonesia - Irdayani; Sri Wahyuni.MS; Hidayana (Community Medicine and Education Journal, 2023)
Perineal rupture is a tear in the tissue located between the vulva and anus that can occur during childbirth. This happens because the bigger the baby is born, the greater the risk of this occurring rupture perineum due to the large birth weight of the baby. This study aimed to find out the risk factor for perineal rupture in normal maternity mothers at BPM Barirah Madeni, Central Aceh Regency, Indonesia. This research is an analytical survey with a cross-sectional approach, with the population being all mothers giving birth normally at BPM Barirah Madeni, totaling 94 people. The samples taken were the entire population, namely 94 people. Data was collected using a questionnaire and then analyzed univariate and bivariate. The results of the study showed that there was a relationship between birth weight and perineal rupture in normal labor and outcomes p-value = 0.001 (p<0.05). However, there is no relationship between partus precipitatus and the incidence of perineal rupture in normal maternity women, with the results p-value = 0.192 (p>0.05).